Revitalisasi Pengelolaan Asrama Dalam Mengembangkan Pendidikan Katolik Bagi Suku Dayak di Wilayah Perbatasan Kabupaten Sanggau - Suko suko; Felisitas Yuswanto (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2021)
Boarding schools combine the residences of students in school institutions away from home and family, religiously taught and taught several subjects according to the educational curriculum. This article aims to de-describe the discussion about the quantity and quality of Dayak students living in dormitories today, find the factors that cause the lack of interest of children to live in dormitories, and the Involvement of the Catholic Church in revitalizing dormitories in developing education for dayak tribes in the Border Region of the Diocese of Sanggau. The method used is qualitative with data sources of dormitory managers, dormitory children sons / daughters and children who do not live in dormitories. Data obtained from observations, interviews, and documentaries. Data is analyzed qualitatively. The results of the study found that the quality and quantity of children who want to live in dormitories is greatly reduced. This is because Catholic schools that have dormitory facilities compete more closely with other educational foundations, lack of guaranteed school and dormitory facilities, weak dormitory discipline, the number of housing offers (boarding schools) or affordable parents/relatives from the school location, catholic school fees that have dormitory facilities are relatively expensive, and the character of students who do not like to be bound by rules that are considered burdensome.